2016
DOI: 10.1111/jwas.12245
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of 2‐phenoxyethanol and Clove Oil for Reducing Handling Stress in Reared Meagre, Argyrosomus regius (Pisces: Sciaenidae)

Abstract: The effect of two anesthetics, 2‐phenoxyethanol (2‐PE) and clove oil (COil) were studied in meagre, Argyrosomus regius. This study aimed to determine the adequate dose of anesthesia for different aquaculture procedures, to assess a sedative or stressor effect of low anesthetic concentrations, and to assess the effect of low anesthetic doses at high fish densities for longer periods of time on fish survival and behavior. Anesthetics were tested at different concentrations: 2‐PE at 100, 250, 400, 550, and 700 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
1
23
0
4
Order By: Relevance
“…There are several studies which try to determine the effective concentrations of clove oil and 2-phenoxyethanol in S. aurata and D. labrax (Mylonas et al, 2005), S. senegalensis (Weber et al, 2009), A. persicus (Adel et al, 2016), A. regius (Barata et al, 2016). However, there is no anesthetic efficacy study in doctor fish regarding these anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies which try to determine the effective concentrations of clove oil and 2-phenoxyethanol in S. aurata and D. labrax (Mylonas et al, 2005), S. senegalensis (Weber et al, 2009), A. persicus (Adel et al, 2016), A. regius (Barata et al, 2016). However, there is no anesthetic efficacy study in doctor fish regarding these anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Mylonas et al (2005), we found that clove oil was effective at 4-fold lower concentrations than 2-phenoxyethanol on doctor fish. Barata et al (2016) explained this situation that clove oil affects different type of receptors might justify a higher efficiency and the use of lower concentrations. It is clear that the clove oil is advantageous because of its plant origin, safe nature, low price, and its effectiveness even at lower concentrations (Mylonas et al, 2005;Javahery et al, 2012;Kizak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After sedation with 800 ppm of 2-phenoxyethanol [64], blood was withdrawn from the caudal vein with a 1 mL heparinized syringe. Collection of blood samples (1 mL of blood per fish, on average) was completed within 3 min after capturing the fish to minimize the effects of handling on stress parameters.…”
Section: Sampling Protocolmentioning
confidence: 99%
“…Under such circumstances, the use of anesthetic agents may be beneficial or even necessary. A number of chemical anesthetics have been used in fishery research, for example, MS-222, clove oil, benzocaine, and 2-phenoxyethanol (Heo and Shin, 2010) (Popovic et al, 2012; Barata et al, 2016). The most commonly used anesthetic in aquaculture practice and research is MS-222 (Popovic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%